1997
DOI: 10.1161/01.atv.17.11.3242
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Angiotensin Converting Enzyme Gene Is Associated With Circulating Levels of Plasminogen Activator Inhibitor-1

Abstract: The deletion (D) allele of the insertion/deletion (I/D) polymorphism of the angiotensin converting enzyme (ACE) gene is strongly associated with an increased level of circulating ACE. The ACE gene polymorphism may influence the production of angiotensin II (Ang II). It has been shown that Ang II modulates fibrinolysis, that is, Ang II increases plasminogen activator inhibitor-1 (PAI-1) mRNA and plasma PAI-1 levels in vitro and in vivo. Considered together, we tested the hypothesis that the deletion allele of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 41 publications
2
44
6
Order By: Relevance
“…9,10,[34][35][36] Several experimental studies have shown that PAI-1 activity is stimulated by angiotensin II, or associated with ACE gene polymorphism, 37 although this latter association has been questioned by others. 38 Thus, antihypertensive drugs acting within the renin-angiotensin system should also exert effects within the fibrinolytic system.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,[34][35][36] Several experimental studies have shown that PAI-1 activity is stimulated by angiotensin II, or associated with ACE gene polymorphism, 37 although this latter association has been questioned by others. 38 Thus, antihypertensive drugs acting within the renin-angiotensin system should also exert effects within the fibrinolytic system.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary insulin inhibits synthesis of PAI-1 in the endothelium induced by TGF-, probably due to activated cGMP and cAMP systems. Insulin along with leptin also stimulates the PAI-1 production in vascular smooth muscles (Eriksson et al, 1998;Hamsten & Eriksson, 1994;Kawai et al, 1996;Kim et al, 1997;Li et al, 1997;Peiretti et al, 1997;Vaughan, 1997Vaughan, , 2005Yamauchi et al, 1997).…”
Section: Pai-1 Vascular Compartmentmentioning
confidence: 99%
“…16 The studies in the literature on this subject are contradictory. In this study, we investigated the effects of ACE gene polymorphism, thrombophilic factor gene polymorphisms, and homocysteine level on AVF function in HD patients.…”
Section: Introductionmentioning
confidence: 99%